Hybrid institutions: applications of common property theory beyond discrete property regimes - German, L.; Keeler, A. (2010)
Property rights theory has contributed a great deal to global understanding of the factors shaping the management, governance and sustainability of discrete property regimes (individual, State, commons). Yet as the commons become increasingly altered and enclosed and management challenges extend beyond the boundaries of any given unit of property, institutional theory must extend beyond discrete property regimes. This paper argues that as natural resource management challenges grow more complex and interconnected, common property theory in the Ostrom tradition remains an essential component of successful management solutions – for common pool resources, public and private goods alike. Building on the commons and externality literature in general, and the Ostrom and Coasean traditions in particular, we propose the use of the term “hybrid institution” to explore the governance of common or connected interests within and between diverse property regimes. Following a general introduction to a set of propositions for encompassing this expanded realm of application of commons theory, we use the literature on integrated natural resource management to frame the scope of “commons” issues facing rural communities today. Empirical and action research from eastern Africa and logical arguments are each used to illustrate and sharpen the focus of our propositions so that they can be tested and refined in future research. This analysis demonstrates the instrumental potential of the concept of hybrid institutions as a framework for shaping more productive engagements with seemingly intractable natural resource management challenges at farm and landscape scale. Our analysis suggests that central elements of the Ostrom and Coasean traditions can be complementary explanatory lenses for contemporary resource conflict and management.